Behavioral interventions for waste reduction: a systematic review of experimental studies - Wilson, Brent M.; Delmas, Magali A.; Rajagopal, Deepak (Frontiers in Psychology, 2025)
IntroductionWasteful behavior poses major environmental, economic, and social challenges, yet the behavioral science literature on waste reduction remains fragmented.MethodsThis systematic review synthesizes 99 experimental and quasi-experimental studies published between 2017 and 2021 that test behavioral interventions to reduce waste. This period captures a critical phase when global waste management systems faced unprecedented disruptions, including the 2017 launch of China’s National Sword policy, which dramatically reshaped global recycling markets and exposed critical weaknesses in international waste systems. We adopt a broad definition of waste—including both discarded materials (e.g., food, trash, recyclables) and inefficient resource use (e.g., electricity, water, fuel)—to better capture the full range of behaviors where interventions can reduce environmental impact and allow cross-domain comparisons. Our goal is to examine the behavioral interventions used, how interventions are structured, how behavior is measured, and whether they target individuals, households, communities, or broader systems.ResultsWe identify six common types of behavioral interventions: education/informational feedback, social norms, economic incentives, cognitive biases and choice architecture, goal setting, and emotional appeals. Interventions targeting electricity and water use were most common, while food and solid waste remain under studied, largely due to measurement challenges. Although most studies used real-world field designs with direct behavioral outcomes, they focused heavily on individual and household behavior.DiscussionThis individual focus risks overlooking the structural and systemic changes needed to achieve broader, sustained reductions in waste. To advance the field, we call for greater use of community-level and system-wide interventions, investment in scalable measurement tools, and stronger collaboration between researchers, governments, and practitioners. Building on this foundation can help create more effective, scalable strategies to reduce waste across behavioral contexts.